2021
DOI: 10.1186/s12889-021-11211-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family planning outcomes in northwestern Nigeria: analysis and modeling of social and behavior change factors

Abstract: Background Northwestern Nigeria faces a situation of high fertility and low contraceptive use, driven in large part by high-fertility norms, pro-natal cultural and religious beliefs, misconceptions about contraceptive methods, and gender inequalities. Social and behavior change (SBC) programs often try to shift drivers of high fertility through multiple channels including mass and social media, as well as community-level group, and interpersonal activities. This study seeks to assist SBC progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…This study uses nationally representative data from Nigeria and Zambia to explore associations between collective norms and individual modern contraceptive use and how these differ for men and women. Previous studies in both countries have shown that socio-cultural factors play a significant role in forming norms that impact fertility-related behavior, including norms related to gender, desire for larger families, and broader religious/cultural influences 16,[23][24][25][26][27][28] . Gender norms associated with modern contraceptive use include gender-equitable attitudes towards household decision-making, couples' family planning decisions, and community-level family planning self-efficacy in Nigeria 16 and higher mean age at first birth, community justification for domestic violence, the ratio of men's to women's employment in Zambia 15,29 .…”
Section: Introductionmentioning
confidence: 99%
“…This study uses nationally representative data from Nigeria and Zambia to explore associations between collective norms and individual modern contraceptive use and how these differ for men and women. Previous studies in both countries have shown that socio-cultural factors play a significant role in forming norms that impact fertility-related behavior, including norms related to gender, desire for larger families, and broader religious/cultural influences 16,[23][24][25][26][27][28] . Gender norms associated with modern contraceptive use include gender-equitable attitudes towards household decision-making, couples' family planning decisions, and community-level family planning self-efficacy in Nigeria 16 and higher mean age at first birth, community justification for domestic violence, the ratio of men's to women's employment in Zambia 15,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Out of a total of more than 170 countries, Nigeria is among the 20 countries with the highest fertility rates in the world (Niger has the highest rate, with an average of seven children per woman (Hutchinson et al, 2021; World Bank, 2020). The resulting unsustainable population growth has a significant negative impact on people’s lives and on society at large.…”
Section: Introductionmentioning
confidence: 99%
“…With 814 deaths per 100,000 live births (World Health Organization, 2018), Nigerian women have a 1 in 22 life-time risk of dying during pregnancy, childbirth, postpartum or post-abortion and are 500 times more likely to lose their life in childbirth than their counterparts in the most advanced nations of the world ( Daily Trust Report , 2021). Although the degree of the risk varies across the six geopolitical regions of the country, maternal mortality poses a great risk to the health and well-being of Nigerian women and infants (see Hutchinson et al, 2021; National Population Commission and ICF (2019)).…”
Section: Introductionmentioning
confidence: 99%
“…27 , 28 The ideational model has been used to successfully examine and develop health communication campaigns to address HIV, 29 malaria, 30 pandemic influenza, 31 pneumonia, 32 and even contraceptive use. 33 , 34 …”
Section: Introductionmentioning
confidence: 99%